Psychological and neurocognitive impact of Behcet's disease - Caroline A Fisher (International Journal of Vascular Surgery and Medicine - Peertechz Publications, 2020)
Background: Behcet's disease is a vasculitis, causing multisystem inflammation and resulting in oral and genital ulcers and eye and skin lesions. A proportion of suffers also have neurological involvement, termed neuro-Behcet's disease. The purpose of this review was to investigate the psychological and neurocognitive sequelae associated with Behcet's and neuro-Behcet's disease and provide directions for future research.  Results: Depression and anxiety are the most researched psychological conditions in Behcet's disease and appear to be the most consistently observed disorders across studies. Depression and anxiety severity is significantly higher relative to controls, and rates are similar across Behcet's and neuro-Behcet's cohorts. A systematic review would be helpful to fully determine the magnitude of these psychological disorders in Behcet's disease and elucidate correlated clinical, regional and demographic factors. Further research is also needed into somatic and psychotic conditions as existing studies have yielded inconsistent results.  Attenuations in neurocognitive functioning appear to be on a continuum. Reduced cognitive functioning is observed in Behcet's disease relative to healthy controls; however, it is observed more frequently in neuro-Behcet's disease, and in a broader range of neurocognitive domains (visual-spatial abilities, working memory, acquired knowledge, processing speed, long-term memory encoding and retrieval). Methodological limitations in existing studies, thus far, have not allowed for further synthesis of the data, such as through meta-analysis, and the field would benefit from several large-sample, multi-site studies using broad cognitive assessment batteries.  Conclusions: Assessments of psychological functioning should be included as part of routine practice in clinics treating patients for Behcet's disease. The potential for neurocognitive impairment should also be considered, particularly in those with neuro-Behcet's. Appropriate referral pathways for psychiatric, psychological or neuropsychological intervention and treatment can then be offered, so that the psychological and neurocognitive needs in this patient cohort can be appropriately met.